Tolerability and efficacy of the cancer vaccine UV1 in patients with recurrent or metastatic PD-L1 positive head and neck squamous cell carcinoma planned for first-line treatment with pembrolizumab – the randomized phase 2 FOCUS trial - Brandt, Anna; Schultheiss, Christoph; Klinghammer, Konrad; Schafhausen, Philippe; Busch, Chia-Jung; Blaurock, Markus; Hinke, Axel; Tometten, Mareike; Dietz, Andreas; Müller-Richter, Urs; Hahn, Dennis; Alt, Jürgen; et al. (Frontiers in Oncology, 2024)
Background Globally, head and neck squamous cell carcinoma (HNSCC) is the seventh most common malignancy. Despite aggressive multimodal treatment approaches, recurrent and/or metastatic (R/M) disease develops in >50% of patients. In this setting, pembrolizumab was approved for patients with PD-L1 expression. However, response rates with checkpoint inhibitor monotherapy remain limited and strategies to strengthen tumor-directed immune responses are needed. Objective The FOCUS trial is designed to estimate the effectiveness of UV1 vaccination in combination with pembrolizumab versus pembrolizumab as a single agent in patients with R/M HNSCC. Methods and analysis The FOCUS trial is a two-armed, randomized, multicenter phase II study which was designed to evaluate the efficacy and feasibility of the hTERT-targeted cancer vaccine UV1 as add-on to pembrolizumab in the 1st line treatment of patients with R/M PD-L1 positive (combined positive score ≥1) HNSCC. Secondary objectives are the exploration of patient subgroups most likely deriving benefit from this novel combination and the establishment of liquid biopsy tumor monitoring in HNSCC. Ethics and dissemination This clinical study was designed and will be conducted in compliance with Good Clinical Practice and in accordance with the Declaration of Helsinki. It is intended to publish the results of this study in peer-reviewed scientific journals and to present its content at academic conferences. Conclusions A significant number of patients with R/M HNSCC are frail and may not tolerate chemotherapy, these patients may only be suitable for pembrolizumab monotherapy. However, long term disease stabilizations remain the exception and there is a need for the development of efficacious combination regimens for this patient population. The FOCUS study aims to optimize treatment of R/M HNSCC patients with this promising new treatment approach. Clinical Trial Registration https://clinicaltrials.gov/study/NCT05075122, identifier NCT05075122.